Introducing a new post-processing tool for the SWAT+ model to evaluate environmental flows. (February 2021) - Senent-Aparicio, Javier; George, Chris; Srinivasan, Raghavan
Abstract: This paper describes a post-processing tool included in the globally used SWAT model for desktop assessment of environmental flows. The tool uses daily flow data from SWAT outputs and can apply different methodologies based on percentiles or moving averages to assess environmental flows. This tool, included in the visualization section of the SWAT model, is open source and can therefore be readily expanded to include additional methodologies. The features and capabilities of this tool are demonstrated through an application to the Eo River basin in the northwest of Spain. The impact of climate change on environmental flows was analyzed, obtaining reductions in environmental flows significantly greater than those of average flows mainly as a result of the increase in the variability of the daily flow series. This tool can help policymakers and scientists with rapid preliminary assessment of environmental flows. Highlights: A new tool is introduced to facilitate the calculation of environmental flows from SWAT + outputs. Hydrological methods based on moving averages and percentiles are easily calculated. The tool is tested in a 700 km 2 river basin in the Eo river basin (NW Spain).